Challenging Dominant Discourses on Abortion From a Radical Feminist Standpoint. (February 2015) - Gilbert, Indira; Sewpaul, Vishanthie
The article, which is based on the narratives of 15 women in the Durban metropolitan area, contests liberal feminist views of abortion resting on the free choice of women. Adopting a radical feminist standpoint, it locates the abortion decision within structural constraints on women's lives, raising the relationship between socioeconomic freedom and women's reproductive health choices. The article also contests the popular pro-life/pro-choice dichotomy, interrogates the influence of popular pronatalism and discourses on motherhood on women's choices, and highlights feminist relational ethical thinking that underscores women's choices even as they acknowledge principled ethical concerns around the sanctity of life.